Systematic review of addiction recovery mutual support groups and Indigenous people of Australia, New Zealand, Canada, the United States of America and Hawaii. (November 2019) - Dale, Elizabeth; Kelly, Peter J.; Lee, K.S. Kylie; Conigrave, James H.; Ivers, Rowena; Clapham, Kathleen
Abstract: Background: Addictions contribute significantly to the overall disease burden for Indigenous peoples of colonised countries. Mutual support groups are one of the most common addiction recovery resources, however their effectiveness for Indigenous peoples is unclear. Methods: A PRISMA-informed search was performed to retrieve empirical studies on addiction recovery mutual support groups for Indigenous peoples of Australia, New Zealand, Canada, United States of America and Hawaii. Databases searched were: MEDLINE, CINAHL Plus, PsychINFO, PsychARTICLES, SocINDEX, Cochrane Database of Systematic Reviews, PubMed, Scopus and UlrichsWeb, Informit Collections, Australian Indigenous HealthInfonet and Lowitja Institute electronic databases. Exclusion criteria were: 1) not an Indigenous focus; 2) not an addiction focus (i.e. including alcohol, other drug, gambling); 3) not a mutual support group focus; 4) not an original study; 5) not a complete study; 6) not published in English language. Results: Four studies published between 2001 and 2006 met review criteria. All studies were conducted in the United States of America with Native American Indian peoples ( n  = 1600) and featured Alcoholics Anonymous only. Study designs were: a retrospective analysis of survey data, a cross-sectional survey report, a clinical case study and an ethnographic study. Methodological differences precluded meaningful translation of results. Conclusion: There is a lack of empirical knowledge on the acceptability and outcomes of addiction recovery mutual support groups for Indigenous peoples of Australia, New Zealand, Canada, United States of America and Hawaii. This review suggests recommendations for future research. Highlights: Indigenous people of similarly colonised countries experience high rates of morbidity and mortality due to addictions Mutual support groups are a common and popular form of addiction recovery support Few studies have evaluated the utility of mutual support groups for Indigenous members Mutual support groups may become a more meaningful resource for Indigenous people if they were culturally modified